Impact of Plastic Debris on the Gut Microbiota of Caretta caretta From Northwestern Adriatic Sea - Biagi, Elena; Musella, Margherita; Palladino, Giorgia; Angelini, Valeria; Pari, Sauro; Roncari, Chiara; Scicchitano, Daniel; Rampelli, Simone; Franzellitti, Silvia; Candela, Marco (Frontiers in Marine Science, 2021)
Plastic pollution is nowadays a relevant threat for the ecological balance in marine ecosystems. Small plastic debris (PD) can enter food webs through various marine organisms, with possible consequences on their physiology and health. The loggerhead sea turtle (Caretta caretta), widespread across the whole Mediterranean Sea, is a ‘flagship species’, useful as indicator of the general pollution level of marine ecosystems. Ingested PD accumulate in the final section of turtles’ digestive tract before excretion. During their transit and accumulation, PD also interact with the residing microbial community, with possible feedback consequences on the host’s health. To explore the possible relationship between fecal microbial composition and PD ingestion, we collected fecal samples from 45 turtles rescued between 2017 and 2019 in the Northwestern Adriatic Sea (Italy), assessing occurrence and content of PD in the samples and in parallel the microbiome structure by 16S rRNA gene sequencing. According to our findings, almost all samples contained PD, mirroring the high level of plastic pollution in the area. We identified phylotypes associated to a high amount of PD, namely Cetobacterium somerae and other taxa, possibly responding to contamination by plastic-associated chemicals. Furthermore, putative marine pathogens were found associated to higher plastic contamination, supporting the hypothesis that PD can act as a carrier for environmental pathogenic bacteria into marine organisms. Besides confirming the role of the sea turtle as relevant flagship species for plastic pollution of the marine environment, our study paves the way to the exploration of the impact that PD ingestion can have on the microbial counterpart of large marine organisms, with potential feedback consequences on the animal and ecosystem health.